Unaccompanied minors in the European Union - definitions, trends and policy overview - Bernd Parusel (Social Work and Society)
This article provides an overview regarding the increased arrival of unaccompanied minors (UAM) in the Member States of the European Union over recent years and clarifies the role of the EU and its institutions in regulating this particular migratory phenomenon. It summarizes how the entry and stay of UAM has become a policy topic for the EU and what the Union's supra-national laws and policies say about these minors' rights and entitlements in the context of immigration and asylum processes. The article points out progresses and failures, protection gaps, and challenges that still need to be addressed, such as the unequal distribution of UAM across the Member States and unsatisfactory policy outcomes for those who remain outside asylum procedures or turn 18 during the process. Finally, it finds that the search for durable solutions for UAM risks to be overshadowed by short-term emergency measures and changing policy frameworks.